HUBUNGAN ACNE VULGARIS DENGAN BODY IMAGE PADA REMAJA DI SMA FAJRUL ISLAM JAKARTA - Maftuh Fiiha Fakihatun; Beata Rivani; Sondang Derimaulina Pasaribu (STIKes IMC Bintaro, 2019)
Acne vulgaris is a chronic inflammatory disease characterized by blackheads, papules, pustules, nodules, cysts often found in predilected areas such as the face, upper shoulder of the superior extremity, chest and back which causes changes in body image in adolescents. Teenagers who have a positive outlook on the appearance of acne will form a positive body image, while teens who have a negative view of the appearance of acne will form a negative body image. The purpose of this study was to determine the relationship of acne vulgaris with body image in adolescents at Fajrul Islam High School Jakarta. This type of research is observational analytic with a correlation research design with a Cross-Sectional approach. The study sample consisted of 146 students of class X, XI, and XII. The sampling method is simple random sampling. This research was conducted in March 2019. The analysis used was Chi-Square statistical test. Results: The results of this study indicate that there is a relationship between acne vulgaris and body image in adolescents with a p value = 0.002 (p <0.05). Conclusion: There is a relationship between acne vulgaris and body image in adolescents. Suggestion: For the school environment such as the teacher as the closest teenager in school, so that it gives more positive things and responds to support in every change that occurs, especially face changes because the response from the closest people can improve the body image of the teenager.